(untitled) (Revista de Ciências Agroveterinárias, 2013)
Tomato crops are very susceptible to pests, which in conventional control measures have required the use of a lot of pesticides. The aim of this work was to evaluate the effect of high dilution preparations on the incidence of insects in the tomato crops under organic production systems. Experiments were carried out under fi eld conditions during 2008/2009 and 2009/2010 crop cycles. The treatment consisted of high dilution preparations of Staphysagria, Arsenicum album, Sulphur, Arnica montana, biotherapic of Solanum lycopersicum and biotherapic of Solanum aculeatissimum. All of them were applied at decimal (DH) and centesimal (CH) hahnemaniann dilution order. Bordeaux mixture, cupric preparation and Bacillus thuringiensis were also included. It was observed that coleoptera insects and thrips were sporadically present but Agathomerus sellatus was regularly found in all treatment. The population of A. sellatus was significantly reduced by Sulphur and Arnica montana, respectively to 12 and 24 DH high dilutions. High dilution preparations have the potential to reduce insect incidence on tomato crops and it can be effective control measure for Agathomerus sellatus.